Impact of climate change on physiology of medicinal and aromatic plants - Kalariya, K A; Shahi, Deepa; Das, Manish (Indian Horticulture, 2023)
Medicinal plants are valuable resources for drug development and therapeutic nutrition, supporting health care and livelihood of tribal and rural communities. Global warming, caused by increased greenhouse gas emissions leads to change in climate resulting in altered seasonal patterns, weather events, and temperature ranges worldwide, which is a significant concern for agriculture. Agriculture contributes to greenhouse gas emissions, with nitrogenous fertilizers and deforestation being major sources of N2O emissions. Greenhouse gases like CH4 and N2O have a much higher radiative impact than CO2, exacerbating global warming. Changing climate conditions impose various abiotic stresses on medicinal plants, affecting their growth and secondary metabolism. The response of medicinal plants to stress varies depending on the species, growth stage and environmental conditions, making it challenging to define an optimum stress condition for quality produce. This article describes the impact of climate change on physiology of medicinal and aromatic plants.